Identification and Expression Profiling of Chemosensory Genes in Dendrolimus punctatus Walker - Zhang, Su-fang; Liu, Hui-hui; Kong, Xiang-bo; Wang, Hong-bin; Liu, Fu; Zhang, Zhen (Frontiers in Physiology, 2017)
Dendrolimus punctatus Walker is a serious pest affecting conifers in southern China. As extensive pesticide spraying is currently required to control D. punctatus, new control strategies are urgently needed. Chemosensory genes represent potential molecular targets for development of alternative pest control strategies, and the expression characteristics of these genes provide an indication of their function. To date, little information is available regarding chemosensory genes in D. punctatus or their expression profiles at different development stages and in various tissues. Here, we assembled and analyzed the transcriptomes of D. punctatus collected at different developmental stages and in a range of organs, using next-generation sequencing. A total of 171 putative chemosensory genes were identified, encoding 53 odorant binding proteins, 26 chemosensory proteins, 60 odorant receptors, 12 gustatory receptors, 18 ionotropic receptors, and 2 sensory neuron membrane proteins. Expression analysis indicated that the antennae possess the largest number of highly expressed olfactory genes and that olfactory gene expression patterns in the eggs, larvae, and head were similar to one another, with each having moderate numbers of highly expressed olfactory genes. Fat body, ovary, midgut, and testis tissues also had similar olfactory gene expression patterns, including few highly expressed olfactory genes. Of particular note, we identified only two pheromone binding proteins and no pheromone receptors in D. punctatus, similar to our previous findings in Dendrolimus houi and Dendrolimus kikuchii, suggesting that insects of the Dendrolimus genus have different pheromone recognition characteristics to other Lepidopteran insects. Overall, this extensive expression profile analysis provides a clear map of D. punctatus chemosensory genes, and will facilitate functional studies and the development of new pest control methods in the future.